2020
DOI: 10.1002/jcla.23482
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib induces primary ectopic endometrial cell apoptosis through up‐regulation of STAT1 in vitro

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…In recent years, studies have found that STAT1 may act as a tumor promoter (39), suggesting that the function of STAT1 might change with the cellular and external environment (40). Elevation of p-STAT1 has previously been reported to promote apoptosis of ectopic endometrial stromal cells (41). We found that the effect of HK2 on cell proliferation was partially dependent on p-STAT1.…”
Section: Discussionsupporting
confidence: 55%
“…In recent years, studies have found that STAT1 may act as a tumor promoter (39), suggesting that the function of STAT1 might change with the cellular and external environment (40). Elevation of p-STAT1 has previously been reported to promote apoptosis of ectopic endometrial stromal cells (41). We found that the effect of HK2 on cell proliferation was partially dependent on p-STAT1.…”
Section: Discussionsupporting
confidence: 55%
“…In this context, Li et al [38] showed that the upregulation of caspase-3 expression is concomitant with and correlated to the expression of the signal transducer and activator of transcription 1 (STAT1), which is also an important signal molecule in inflammatory response modulation. In addition, in a study of the potential beneficial effect of Kuntai Capsule (KTC) on apoptosis, Zhong et al [39] showed that the modulation of caspase-8, caspase-9, caspase-3, and cytochrome could promote apoptosis in the EMS tissues.…”
Section: Apoptosis and Emsmentioning
confidence: 99%